The influence of an anti‐inflammatory diet on gingivitis. A randomized controlled trial. (2nd April 2019) - Woelber, Johan P.; Gärtner, Maximilian; Breuninger, Lilian; Anderson, Annette; König, Daniel; Hellwig, Elmar; Al‐Ahmad, Ali; Vach, Kirstin; Dötsch, Andreas; Ratka‐Krüger, Petra; Tennert, Christian
Abstract: Aim: Aim of this study was to investigate the influence of an anti‐inflammatory diet on different parameters in patients with gingivitis. Materials and Methods: Thirty patients were randomly allocated to an experimental and a control group stratified by their plaque values. The experimental group had to change to a diet low in processed carbohydrates and animal proteins, and rich in omega‐3 fatty acids, vitamin C, vitamin D, antioxidants, plant nitrates and fibres for 4 weeks. The control group did not change their diet. Both groups suspended interdental cleaning. Periodontal parameters were assessed by a blinded dentist. Serological and subgingival plaque samples were taken at baseline and end. Results: While there were no differences regarding the plaque values, the experimental group showed a significant reduction in gingival bleeding (GI Baseline: 1.04 ± 0.21, GI End: 0.61 ± 0.29, p < 0.05), a significant increase in Vitamin D values and a significant weight loss. There were no inter‐group differences regarding the inflammatory serological parameters, the serological omega fatty acids, nor the subgingival microbiome composition. Conclusion: The evaluated diet could significantly reduce gingivitis in a clinically relevant range, while serological inflammatory parameters and the subgingival microbiome seem to be unaffected in this study duration. (German Clinical Trials Register; DRKS00009888).